Eric C. Miller and Jonathan J. Edwards, eds., Rhetoric of the Protestant Sermon in America: Pulpit Discourse at the Turn of the Millennium: Lexington Books, 2020 (Homiletic, 2020)
Please click the PDF button to access the review.